Синтез волокнистого поліпропіленового адсорбента із закріпленими на поверхні наночастинками гідратованого оксиду заліза - Bondar, Yu. V.; Kuzenko, S. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2013)
Results on synthesis of hybrid adsorbent by the in-situ formation of hydrated ferric (III) oxides nanoparticles on the surface of modified polypropylene are discussed. Scanning electron microscope investigations have revealed that hydrated ferric oxides form a homogeneous compact layer of nanosized agglomerates. Adsorption of uranyl ions onto synthesized fibers from acidic solutions has been carried out.